Healthcare-seeking behaviour of HIV-infected mothers and male partners in Nairobi, Kenya - Drake, Alison L. (Glob Public Health, 2015)
Healthcare-seeking behaviours of HIV-infected mothers in sub-Saharan Africa are poorly characterized and typically focus on individual health conditions rather than overall health. We conducted a qualitative study to understand how HIV-infected mothers, their male partners, and their HIV-exposed infants seek medical services. We performed 32 in-depth interviews (17 female, 15 male) and four focus group discussions (FGDs) among HIV-infected postpartum women and their male partners in Nairobi, Kenya. We used a grounded theory approach to explore the paths followed for health-related concerns. Female participants reported that willingness to be tested for HIV influences whether women sought antenatal care and the type of facility they preferred for childbirth. The need for medical care outside regular clinic hours and securing safe transportation at night were also significant barriers to seeking care. Most men sought services from traditional healers and chemists before HIV diagnosis, and at governmental facilities afterwards. Both men and women sent infants to traditional healers for non-medical conditions such as bewitching and massage, but rarely for medical conditions. Strategies to reduce HIV-related stigma and fears in antenatal and maternity settings, increase access to care after-hours, and improve linkage to HIV care for men early in their infection are needed.